Development of Self-Learning Instructional Material and its Effecto on Academic Achievement in Mathematics of Class Eight Students - Mittal, Priyanka (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Introduction-Mathematics is an important subject in the school curriculum. It is more closely related to our daily life as compared to other subjects. Except for our mother tongue, there is no other subject which is more closely related to our daily life as mathematics. According to National Policy on Education (1986) "Mathematics should be visualized as the vehicle to train a child to think, reason, analyze and articulate logically".  Objectives-The objectives of the study are: 1. To develop self-learning instructional material of mathematics for class eight students. 2. To find out the effect of the developed self-learning instructional material of mathematics on academic achievement in mathematics of class eight students.  Method and Procedure-The researcher used the developmental method followed by the experimental method. So the research design consisted of two phases, viz., Developmental phase and Experimental phase. The selection of the school was kept purposive because only coeducation school having two sections could meet the researcher‘s experimental needs. Self- Made Rating Scale: For Validation of Self Learning instructional material (SLIM) in mathematics and Academic achievement test (Post-test) of mathematics used by the researcher. Result and Discussion- Finally, concluded that significant effect of self-learning instructional material was found on academic achievement in mathematics of class eight students. Conclusion- The main finding of the study was that there was a significant effect of the teaching based on self-learning instructional material. It was found that the students who were exposed to the self- learning instructional material performed significantly better in mathematics than the students who were taught by conventional method. It is due to the development of mental faculties of the students by reasoning, logical thinking, self-motivation (applications of selflearning instructional material). Implication- Studying mathematics by using Self-learning instructional material will help the students to learn mathematics in a systematic way further it will help the students to learn with their own capacity and their own speed.